NAWAL AL-SA’ADAWI DALAM PEREMPUAN DAN SEKS; PERSOALAN KHITAN BAGI PEREMPUAN DITINJAU DARI KESEHATAN DAN ISLAM - Fuad Mahbub Siraj (Jurnal Universitas Paramadina, 2014)
AbstractNawal al-Sa'adawi is a doctor from Egypt who is also famous as a writer,  novelist and feminist. He raised the issue of gender in his work Almar'ah wa  al-Jins (Women and Sex) that associated with the issue of circumcision for  women. Generally in the world and particularly in the Egypt, the emergence of  circumcision became a tradition among the people, the problem that is always  "sue" in the mind of Nawal al-Sa'adawi, because it was thought as  uneliminated heritage. In addition, the circumcision is not come from the doctrine of Islam that must be maintained.